The zoology of the voyage of the H.M.S. Erebus & Terror, under the command of Captain Sir James Clark Ross, during the years 1839 to 1843. By authority of the Lords Commissioners of the Admiralty - Richardson, John, Sir, 1787-1865; Gray, John Edward 1800-1875; Ross, James Clark, Sir, 1800-1862; Erebus (Ship).; Terror (Ship).
2